"I love discussing my work": a case study examining the use of discourse by eighth-grade students in writing workshop - Phelan, Jane, author; O'Donnell-Allen, Cindy, advisor; Ginsberg, Ricki, committee member; Aragón, Antonette, committee member (Colorado State University. Libraries, 2021)
This case study explored the effect of discourse and oral rehearsal of writing on the progress of eighth-grade writers in the workshop model of writing instruction. Through my position of teacher-researcher, I observed three randomly chosen students to determine how learning academic discourse and orally rehearsing writing affected their progress as writers. Results suggested that writing was improved by learning academic discourse and orally practicing writing before putting pen to paper.